ANALISIS KESALAHAN PELAFALAN KATA DALAM PROSES PEMBELAJARAN BAHASA INDONESIA OLEH SISWA KELAS VIII-A DI SMP NEGERI 1 IDANOTAE - Yusni Lase; Anita Zagoto (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
Based on the background of the problem, word pronunciation errors have become a habit for students to pronounce words. This research aims to describe word pronunciation errors in the Indonesian language learning process by class VIII-A students at SMP Negeri 1 Idanotae for the 2022/2023 academic year. The approach used in this research is a case study approach. This research data was analyzed using data reduction, verification and drawing conclusions. The results of this research are the omission (omotion) of seven sentences, the addition (addition) of seven sentences, the misformation of four sentences, the misordering of eleven sentences. Suggestions for future researchers, the results of this research can be used as material for further research on word pronunciation in language.